Potential Metabolite Nymphayol Isolated from Water Lily (Nymphaea stellata) Flower Inhibits MCF-7 Human Breast Cancer Cell Growth via Upregulation of Cdkn2a, pRb2, p53 and Downregulation of PCNA mRNA Expressions - Laila Naif Al-Harbi; Pandurangan Subash-Babu; Manal Abdulaziz Binobead; Maha Hussain Alhussain; Sahar Abdulaziz AlSedairy; Amal A Aloud; Ali A Alshatwi (Metabolites, 2020)
Controlled production of cyclin dependent kinases (CDK) and stabilization of tumor suppressor genes are the most important factors involved in preventing carcinogenesis. The present study aimed to explore the cyclin dependent apoptotic effect of nymphayol on breast cancer MCF-7 cells. In our previous study, we isolated the crystal from a chloroform extract of Nymphaea stellata flower petals and it was confirmed as nymphayol (17-(hexan-2-yl)-10,13-dimethylhexadecahydro-1H-cyclopenta[a]phenanthren-3-ol) using x-ray diffraction (XRD), Fourier transform infrared (FTIR), and mass spectroscopy (MS) methods. The cytotoxic effect of nymphayol on MCF-7 cells were analyzed using the 3-(4,5-dimethylthiazol-2yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. The cellular and nuclear damage was determined using propidium iodide (PI) and acridine orange/ethidium bromide (AO/ErBr) staining. Tumor suppressor and apoptosis related mRNA transcript levels were determined using real-time polymerase chain reaction (RT-PCR). Nymphayol potentially inhibits MCF-7 cell viability up to 78%, and the IC50 value was observed as 2.8 µM in 24 h and 1.4 µM in 48 h. Treatment with nymphayol significantly increased reactive oxygen species (ROS) level and the tunnel assay confirmed DNA damage. We found characteristically 76% apoptotic cells and 9% necrotic cells in PI and AO/ErBr staining after 48 h treatment with 2.8 µM of nymphayol. Gene expression analysis confirmed significantly (p ≤ 0.001) increased mRNA levels of cyclin dependent kinase inhibitor 2A (Cdkn2a), retinoblastoma protein 2 (pRb2), p53, nuclear factor erythroid 2-factor 2 (Nrf2), caspase-3, and decreased B-cell lymphoma 2 (Bcl-2), murine double minute 2 (mdm2), and proliferating cell nuclear antigen (PCNA) expression after 48 h. Nymphayol effectively inhibited breast cancer cell viability, and is associated with early expression of Cdkn2a, pRb2, and activation of p53 and caspases.